Treatment of COVID-19 With Conestat Alfa, a Regulator of the Complement, Contact Activation and Kallikrein-Kinin System - Urwyler, Pascal; Moser, Stephan; Charitos, Panteleimon; Heijnen, Ingmar A. F. M.; Rudin, Melanie; Sommer, Gregor; Giannetti, Bruno M.; Bassetti, Stefano; Sendi, Parham; Trendelenburg, Marten; Osthoff, Michael (Frontiers in Immunology, 2020)
A dysregulated immune response with hyperinflammation is observed in patients with severe coronavirus disease 2019 (COVID-19). The aim of the present study was to assess the safety and potential benefits of human recombinant C1 esterase inhibitor (conestat alfa), a complement, contact activation and kallikrein-kinin system regulator, in severe COVID-19. Patients with evidence of progressive disease after 24 hours including an oxygen saturation <93% at rest in ambient air were included at the University Hospital Basel, Switzerland in April 2020. Conestat alfa was administered by intravenous injections of 8400 IU followed by 3 additional doses of 4200 IU in 12-hour intervals. Five patients (age range, 53-85 years; one woman) with severe COVID-19 pneumonia (11%-39% lung involvement on computed tomography scan of the chest) were treated a median of 1 day (range 1-7 days) after admission. Treatment was well tolerated. Immediate defervescence occurred, and inflammatory markers and oxygen supplementation decreased or stabilized in 4 patients (eg, median C-reactive protein 203 (range 31-235) mg/L before vs. 32 (12-72) mg/L on day 5). Only one patient required mechanical ventilation. All patients recovered. C1INH concentrations were elevated before conestat alfa treatment. Levels of complement activation products declined after treatment. Viral loads in nasopharyngeal swabs declined in 4 patients. In this uncontrolled case series, targeting multiple inflammatory cascades by conestat alfa was safe and associated with clinical improvements in the majority of severe COVID-19 patients. Controlled clinical trials are needed to assess its safety and efficacy in preventing disease progression.